2007
DOI: 10.1007/s00022-007-1915-x
|View full text |Cite
|
Sign up to set email alerts
|

Examples of a generalization of contact metric structures on fibre bundles

Abstract: We consider a Riemannian manifold with a compatible f -structure which admits a parallelizable kernel. With some additional integrability conditions it is called (almost) K, C, S-manifold and is a natural generalization of the (almost) contact metric and the Sasakian manifolds. There are presented various methods of constructing examples of such manifolds. There are used structures on the principal bundles and the pull-back bundles. Then there are considered relations between (almost) K, C, S-manifolds and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The manifold U (2) is compact, connected, with Euler number χ(U (2)) = 0, thus we can define a left-invariant Lorentz metric g such that the vector fields ξ 1 , ξ 2 , X and Y form an orthonormal basis with g(ξ 1 , ξ 1 ) = −1. Such a structure on U (2) is constructed in the Riemannian context ( [11]) and then it is adapted to the Lorentzian case ( [7]).…”
Section: Null Osserman Condition and Lorentz S-manifoldsmentioning
confidence: 99%
“…The manifold U (2) is compact, connected, with Euler number χ(U (2)) = 0, thus we can define a left-invariant Lorentz metric g such that the vector fields ξ 1 , ξ 2 , X and Y form an orthonormal basis with g(ξ 1 , ξ 1 ) = −1. Such a structure on U (2) is constructed in the Riemannian context ( [11]) and then it is adapted to the Lorentzian case ( [7]).…”
Section: Null Osserman Condition and Lorentz S-manifoldsmentioning
confidence: 99%
“…In particular, from (3) we see that E is integrable, hence it defines a foliation £ of M. Therefore we can regard an r-contact manifold as a smooth manifold of dimension 2n + r foliated by an r-dimensional foliation and whose transverse geometry is modelled on a symplectic manifold. We remark that, as pointed out in [9], there are examples of (2n+r)-dimensional smooth manifolds, with r even, which admits an r-contact structure but no symplectic structures, and (2n + r)-dimensional smooth manifolds, with r odd, which admits an r-contact structure but no contact structures.…”
Section: A Generalization Of Contact Manifoldsmentioning
confidence: 54%
“…It is known that U (2) does not admit a Kähler or a symplectic structure; namely, (cf. [8]), its Betti numbers are…”
Section: Proposition 35 the Harmonicity Of Vector Fields Is Invariamentioning
confidence: 99%
“…In [8], it is shown that if s is even, s = 2t, then b 1 is odd, which implies that E 2n+2t cannot carry a Kähler structure for any values n, t ∈ N * . In fact, the first Betti number of…”
Section: Example 32 ([1 8])mentioning
confidence: 99%
See 1 more Smart Citation